Validity and Reliability of Assessment Rubrics of High Service Skill Learning Outcome Test for Elementary School Students - Burhan Hambali; Amung Ma'mun; Budi Susetyo; Yusuf Hidayat; Agus Gumilar (Universitas Pendidikan Indonesia, 2022)
Assessment rubrics of high service skill learning outcome test should have an adequate validity and reliability as a reliable measuring tool. This study aimed to test the validity and reliability level of the assessment rubric of high service skill learning outcome test for elementary school students. The research method used was descriptive quantitative method. The participants of this study were 50 elementary school students aged 11-12 years. The constructed assessment rubric referred to the performance test instrument involving individual performance assessment model. The analysis was administered using the content validity estimation (Lawshe's CVR), test-retest reliability, inter-rater reliability (Interclass Coefficient Correlation), and meta rubric analysis. The results of the analysis showed that the reliability and validity of the assessment instrument had shown a good criteria (p_value 0.05) significantly. Based on the results of reliability and validity tests, it concludes that the compiled assessment rubric can be used to assess the high service skill learning outcomes in badminton learning for elementary school students.